2019
DOI: 10.21203/rs.2.15834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proportion and Determinants of Repeat Induced Abortion Among Women Seeking Abortion Care Services At Debre Markos Town Health Institutions, Amhara Regional State, Ethiopia, 2017

Abstract: Objective the aim of this study was to assess the proportion and determinants of repeat induced abortion among women seeking abortion care services at Debremarkos town health institutions, Amhara regional state, Ethiopia, 2017.Result from the total 567-sample size, 547 women were participated in the study making a response rate of 96.5%. In this study 191 woman reported that they had at least one previous abortion, making the proportion of repeat induced abortion 34.9%. In multivariable logistic regression ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The finding of this work argues that most prevalence of RTA-related death occurred among drivers, followed by pedestrians, and passengers (38), and also the finding of this paper showed that drivers, pedestrians, and passengers were the most victims of RTA-related death. This may be explained by the fact that the road environment in Ethiopia is known to be relatively unsafe and uncomfortable compared to that of higher-income countries and the country has a mix of road users.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The finding of this work argues that most prevalence of RTA-related death occurred among drivers, followed by pedestrians, and passengers (38), and also the finding of this paper showed that drivers, pedestrians, and passengers were the most victims of RTA-related death. This may be explained by the fact that the road environment in Ethiopia is known to be relatively unsafe and uncomfortable compared to that of higher-income countries and the country has a mix of road users.…”
Section: Discussionsupporting
confidence: 60%
“…It also increases the likelihood of adopting other risky forms of behavior, such as speeding and not using safety equipment such as seatbelts and helmets. (38) Unlikely other results showed that in Tanzania, Kenya, and Ethiopia. (30,35,39) This is due to a lack of good mechanisms for measuring blood alcohol content levels and breathing analyzers for drivers during driving.…”
Section: Discussionmentioning
confidence: 83%